Islamic Religious Education for Women: A Comparative Study of the Thoughts of Rasuna Said and Siti Walidah - Mualifah Macica Putri; Anang Rohwiyono (al-Afkar, Journal For Islamic Studies, 2024)
Nowadays education can be easily obtained, even learning does not need to exist in a formality like in school.  However, during the colonial period the Indonesian people were very difficult to get except only the nobles and rich families. The natives were selected to attend schools that taught only reading, writing, and arithmetic. It was very difficult for Indonesians to get an education in the Dutch colonial era. At that time, the colonizers did not want the Indonesian people to think visionary. However, there are most nobles who have received higher education willing to fight for freedom for Indonesia, so that the Indonesian people get their right to life, they are heroes for Indonesia. Rasuna Said and Siti Walidah succeeded in fighting for the right to receive general education and Islamic education for women in Indonesia.